Co-segregation of hyperactivity, active coping styles, and cognitive dysfunction in mice selectively bred for low levels of anxiety - Yen, Yi-Chun; Anderzhanova, Elmira; Bunck, Mirjam; Schuller, Julia; Landgraf, Rainer; Wotjak, Carsten T. (Frontiers in Behavioral Neuroscience, 2013)
We established mouse models of extremes in trait anxiety, which are based on selective breeding for low vs. normal vs. high open-arm exploration on the elevated plus-maze. Genetically selected low anxiety-related behavior (LAB) coincided with hyperactivity in the home cage. Given the fact that several psychiatric disorders such as schizophrenia, mania and attention deficit hyperactivity disorder (ADHD) share hyperactivity symptom, we systematically examined LAB mice with respect to unique and overlapping endophenotypes of the three diseases. To this end Venn diagrams were used as an instrument for discrimination of possible models. We arranged the endophenotypes in Venn diagrams and translated them into different behavioral tests. LAB mice showed elevated levels of locomotion in the open field test with deficits in habituation, compared to mice bred for normal (NAB) and high anxiety-related behavior (HAB). Cross-breeding of hypoactive HAB and hyperactive LAB mice resulted in offspring showing a low level of locomotion comparable to HAB mice, indicating that the HAB alleles are dominant over LAB alleles in determining the level of locomotion. In a holeboard test, LAB mice spent less time in hole exploration, as shown in patients with schizophrenia and ADHD; however, LAB mice displayed no impairments in social interaction and prepulse inhibition, implying a unlikelihood of LAB as an animal model of schizophrenia. Although LAB mice displayed hyperarousal, active coping styles and cognitive deficits, symptoms shared by mania and ADHD, they failed to reveal the classic manic endophenotypes, such as increased hedonia and object interaction. The neuroleptic haloperidol reduced locomotor activity in all mouse lines. The mood stabilizer lithium and the psychostimulant amphetamine, in contrast, selectively reduced hyperactivity in LAB mice. Based on the behavioral and pharmacological profiles, LAB mice are suggested as a novel rodent model of ADHD-like symptoms.